Association of outdoor artificial light at night with myopia among Chinese adolescents: a representative cross-sectional study - Liu, Ting; Tan, Weixing; Fu, Youjuan; Cheng, Beijing; Tian, Hua; Liu, Can; Wang, Zhixiang; Zhang, Yanting; Guan, Suzhen; Liu, Zhihong (Frontiers in Medicine, 2024)
Background The association between the rapid increase in myopia among adolescents and the amount of outdoor artificial light at night (ALAN) remains unclear. The aim of this study was to investigate the association between outdoor ALAN and myopia in adolescents. Methods Stratified cluster random sampling was used to obtain a sample of 33,160 students (age range: 9–18 years; mean: 13.51 years) with complete data from 120 primary and secondary schools across the Ningxia region in China in 2021. Myopia was defined as a spherical equivalent (SE) ≤−0.5 diopters (D) in at least one eye, determined by automated refractometers without cycloplegia. Outdoor ALAN data were obtained from satellite data and the two-year average outdoor ALAN exposure for each participant was determined by matching it to their school address (home addresses were not available). The association between ALAN and myopia was assessed using multiple logistic regression models and restricted cubic spline (RCS) regression. Stratified analyses were performed by age, sex, residence, school level, and outdoor exercise time. Results The myopia group had higher outdoor ALAN levels than the non-myopia group [median (interquartile spacing): 14.44 (3.88–26.56) vs. 6.95 (1.21–21.74) nanoWatts/cm2/sr]. After adjusting for covariates identified through stepwise regression, it was observed that the prevalence of myopia increased by 4% for every 10-unit change [95% confidence interval (CI): 1.02–1.07]. Compared to the first quantile (Q1) of outdoor ALAN exposure, the odds ratio (OR) of myopia was 1.20 (95% CI: 1.08–1.34) in the fourth quantile. RCS further showed a positive nonlinear relationship between outdoor ALAN exposure and myopia (p for nonlinear <0.001). Stronger effects were not found in subgroup analyses. Conclusion Outdoor ALAN exposure is positively and nonlinearly associated with the prevalence of myopia in adolescents. Controlling outdoor light pollution may constitute a potential strategy to reduce the incidence of myopia in adolescents.